1994
DOI: 10.1080/00332747.1994.11024695
|View full text |Cite
|
Sign up to set email alerts
|

Insight and Psychosocial Treatment Compliance in Schizophrenia

Abstract: Research has suggested that poor insight in patients with schizophrenia is associated with poorer medication compliance and heightened levels of psychopathology. This study examined the relationship of insight to compliance with a work rehabilitation program and with levels of psychopathology and psychosocial functioning. Poor insight was found to be positively associated with fewer weeks of participation and with poorer social skills and personal presentation in the fifth week of work. Poor insight was also a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
56
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(64 citation statements)
references
References 14 publications
8
56
0
Order By: Relevance
“…Lincoln et al (32) showed that insight is correlated with treatment adherence and psychosocial functionality. It is already known that partial insight or absence of insight in patients with schizophrenia impairs treatment adherence (14). Cases with higher insight scores were found to be treatment-adherent in our study.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Lincoln et al (32) showed that insight is correlated with treatment adherence and psychosocial functionality. It is already known that partial insight or absence of insight in patients with schizophrenia impairs treatment adherence (14). Cases with higher insight scores were found to be treatment-adherent in our study.…”
Section: Discussionsupporting
confidence: 64%
“…Moreover, insights of patients with schizophrenia were reported to be worse than patients with schizoaffective disorder and psychotic depression (11). It was also reported that partial or total impairment of insight in patients with schizophrenia diminishes treatment adherence as well (14). Valenstein et al (15) reported in a review that treatment adherence of 40% of patients with schizophrenia is impaired at any given time and this rate will continue to drop during time.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have demonstrated a significant relationship between insight and positive symptoms, both in bipolar disorder and in other mental disorders 14,[37][38][39][40][41][42][43] . However, other authors conclude that reduced insight is not associated with high levels of psychopathology 44,45 . Our research, which represents all manic population in psychiatric treatment in a health catchment area, now establishes a clear association between lack of insight and violence.…”
Section: Discussionmentioning
confidence: 95%
“…In contrast, all longitudinal studies find at least partially significant results, indicating that insight might not be related to present functioning, but that has an impact on improvements in functioning (Schartz et al, 1997). Research in this field also reveals that the long term relationship between insight and functional outcome is likely to be mediated by symptom severity (Lysaker et al, 1994 . The idea of conceptual overlap between insight and ToM was implied in Frith's neurocognitive model of schizophrenia .…”
Section: Insight and Functional Outcomementioning
confidence: 99%